2008
DOI: 10.1159/000151750
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Multiplets

Abstract: Outcomes, both short and long term, differ between singletons and multiplets. Recently, a number of large, well-designed studies have clarified these differences, particularly in light of major changes in perinatal and neonatal care that have influenced changing outcomes. Accordingly, this article will review risks for singletons, twins and higher-order multiples as whole groups and also after correction for gestational age and other potential confounding variables that differ markedly between the groups. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 136 publications
1
39
0
1
Order By: Relevance
“…However, previous studies have suggested that twins had lower risk for cancers of the lung (20, 48, 49), skin (20), colon, and rectum (18, 20, 48). Thus, it does not seem likely that the average lower birth weight and gestational age for twins (50, 51) compared with singletons influence cancer risk, which has also been supported in previous studies (5254). …”
Section: Discussionsupporting
confidence: 73%
“…However, previous studies have suggested that twins had lower risk for cancers of the lung (20, 48, 49), skin (20), colon, and rectum (18, 20, 48). Thus, it does not seem likely that the average lower birth weight and gestational age for twins (50, 51) compared with singletons influence cancer risk, which has also been supported in previous studies (5254). …”
Section: Discussionsupporting
confidence: 73%
“…Compared to singletons or twins, triplets are delayed in growth and cognitive development. There has been limited research on the effects of BW discordance, but it seems that triplets who are discordant in BW are at an even higher developmental risk than other triplets [43,44]. One study found that most triplets without BW discordance have caught up with singleton and twin standards on cognitive and executive functions at age 5.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Nevertheless, knowledge about the well-being, the socio-emotional and behavioral functioning of triplets is quite scarce. 5 While we could not find any study on triplets' HRQoL, there are two longitudinal cohort studies reporting behavioral adjustment of triplets. These studies demonstrated that behavioral problems are reported for early ages (2 years), but improve thereafter.…”
Section: Introductionmentioning
confidence: 81%